Potential Of Butterfly Pea Flower (Clitoria Ternatea) Extract As An Antidiabetic Agent: Literature Review - Lestari, Puput Legia; Ariyanto, Muhammad Wahyu; Nadhiroh, Wafda Safanah; Sulastri, Afianti; Somantri, Budi; Amalia, Linda (An-Najat, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to insulin deficiency or insulin resistance. The global prevalence of diabetes mellitus continues to increase, posing a significant health and economic burden to society. Conventional pharmacological treatments that are currently available often cause unwanted side effects, so alternative therapies that are safer and more effective are needed. This study aims to collect and analyze data related to the effectiveness of flower extract as an antidiabetic agent in reducing blood glucose levels and preventing complications associated with diabetes. The potential of Clitoria ternatea as an antidiabetic agent was explored through a systematic literature review. Article searches were conducted using scientific databases such as Google Scholar, ScienceDirect, and Mendeley with the keywords "Clitoria ternatea AND diabetes AND blood glucose". The inclusion criteria applied included experimental studies conducted on diabetic samples, interventions with bay flower extract administration, and publications within the last 5 years (2021-2025). From a total of 1,858 articles identified, by applying the PRISMA-ScR method, eight articles were obtained that met the inclusion criteria. The results of the analysis showed that flower extract was effective in reducing blood glucose levels in both diabetes-induced experimental animals and diabetic patients. This antidiabetic effect is thought to be due to the flavonoids and other bioactive compounds in butterfly pea flower that act as α-amylase enzyme inhibitors, antioxidants, and anti-inflammatories. These findings indicate the potential of Clitoria ternatea as a promising therapeutic alternative in the management of diabetes mellitus.